Monitoramento Ubíquo de Veículos em Ambientes Urbanos: Um Estudo de Caso em Salvador com SDR e ADS-B - Coelho, José Ângelo Lefundes; Freitas, Allan Edgard Silva; Marques, Manoel Carvalho (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2025.15923, 2025)
The growing demand for urban land mobility solutions has driven the development of vehicle tracking tools as a promising alternative for urban public transport in several parts of the world. A comprehensive literature review, using the Methodi Ordinatio, was carried out through a systematic search in electronic databases such as ScienceDirect, IEEE Xplore, Scopus, and Web of Science. Some articles were selected for a literature reviewthat addresses aspects of vehicle traceability applied in the context of public transport. We propose an approach based on SDR (Software Defined Radio) technology using ADS-B (Automatic Dependent Surveillance-Broadcast), the paper presents the results for a preliminary validation, considering a case study in the city of Salvador, Bahia.